2016
DOI: 10.1021/acs.orglett.6b00529
|View full text |Cite
|
Sign up to set email alerts
|

Rhodium-Catalyzed Cycloisomerization of 2-Silylethynyl Phenols and Anilines via 1,2-Silicon Migration

Abstract: It has been established that a cationic rhodium(I)/BINAP complex catalyzes the cycloisomerization of 2-silylethynylphenols, leading to 3-silylbenzofurans, via 1,2-silicon migration. Similarly, the cycloisomerization of 2-silylethynylanilines, leading to 3-silylindoles, via 1,2-silicon migration was catalyzed by a cationic rhodium(I)/H8-BINAP complex.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
23
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 41 publications
(23 citation statements)
references
References 43 publications
0
23
0
Order By: Relevance
“…For the assembly of the ligands, the additionally functionalized and protected ethinylphenyl building blocks 8 and 9 were either purchased ( 8 ) or synthesized by following a reported procedure ( 9 ), which was a Sonogashira cross‐coupling reaction between triisopropylsilyl (TIPS)‐protected acetylene and 2‐iodophenol …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…For the assembly of the ligands, the additionally functionalized and protected ethinylphenyl building blocks 8 and 9 were either purchased ( 8 ) or synthesized by following a reported procedure ( 9 ), which was a Sonogashira cross‐coupling reaction between triisopropylsilyl (TIPS)‐protected acetylene and 2‐iodophenol …”
Section: Resultsmentioning
confidence: 99%
“…For the assembly of the ligands, the additionally functionalized and protected ethinylphenyl building blocks 8 and 9 were either purchased (8) or synthesized by following a reported procedure (9), which was a Sonogashira cross-coupling reaction between triisopropylsilyl (TIPS)-protected acetylene and 2iodophenol. [34] The first ligand 6 was obtained by a twofold Suzuki reaction between two equivalents of the boronic acid derivative 8 and commercial 2,9-dibromo-1,10-phenanthroline (10). Both reaction partners were refluxed in a toluene/water mixture (6:1) in the presence of tetrakis(triphenylphosphine)palladium [Pd(PPh 3 ) 4 ] as the catalyst and potassium carbonate (K 2 CO 3 ) as the base.…”
Section: Synthesis and Characterizationmentioning
confidence: 99%
“…On the other hand, our research group recently reported a novel method for the synthesis of highly fluorescent organosilicon compounds. In 2016, we reported the rhodium(I)‐catalyzed cycloisomerization of 2‐silylethynyl phenols, leading to 3‐silylbenzofurans through 1,2‐silicon migration involving alkyne‐vinylidene isomerization . As previously reported, whereas reactions involving metal vinylidene formation through 1,2‐silicon migration typically require high temperature (≥90 °C), it is noteworthy that the above reaction proceeds under mild conditions (room temperature to 80 °C).…”
Section: Introductionmentioning
confidence: 99%
“…[2] As migrating functional groups,s ilyl groups connected with alkynes can undergo 1,2migration via alkyne-allene [3,4] or alkyne-vinylidene isomerization. [5][6][7][8] Gevorgyan reported ag old(I)-catalyzed cycloisomerization of 4-silyl homopropargylic ketones to 3-silylfurans involving 1,2-silicon migration via alkyne-allene isomerization. [3] Our research group subsequently reported the rhodium(I)-catalyzed cycloisomerization of 2-silylethynyl phenols to give 3-silylbenzofurans in areaction involving 1,2silicon migration via alkyne-vinylidene isomerization (Scheme 1, top).…”
mentioning
confidence: 99%
“…[3] Our research group subsequently reported the rhodium(I)-catalyzed cycloisomerization of 2-silylethynyl phenols to give 3-silylbenzofurans in areaction involving 1,2silicon migration via alkyne-vinylidene isomerization (Scheme 1, top). [5,6] On the other hand, Ogoshi and coworkers recently reported an ovel nickel(0)-catalyzed cycloisomerization of ortho-aryl-(or vinyl-/alkynyl-) silylbenzaldehydes,l eading to 3-aryl-(or vinyl-/alkynyl-) 2,1-benzoxasiloles through 1,3-carbon (arene,e thylene,o ra lkyne) migration via the formation of hypervalent silicon centers with h 2 -aldehyde nickel complexes (Scheme 1, middle). [7,8] Despite active research on the development of the migratory cycloisomerization reactions,t ransition-metal-catalyzed cycloisomerization involving both silicon and carbon migration has not been reported to date.H erein, we disclose an unprecedented cationic rhodium(I)/biphep complex cata-lyzed cycloisomerization of 2-alkynylsilylethynylphenols, which leads to alkynylmethylidene-benzoxasiloles via the formation of rhodium vinylidenes through 1,2-silicon migration, followed by 1,3-carbon (alkyne) migration via the formation of hypervalent silicon centers (Scheme 1, bottom).…”
mentioning
confidence: 99%